MRI-based deep learning can discriminate between temporal lobe epilepsy, Alzheimer’s disease, and healthy controls - Allen J. Chang; Rebecca Roth; Eleni Bougioukli; Theodor Ruber; Simon S. Keller; Daniel L. Drane; Robert E. Gross; James Welsh; Anees Abrol; Vince Calhoun; Ioannis Karakis; Erik Kaestner; et al. (Communications Medicine, 2023)
Chang et al. classify people with Temporal Lobe Epilepsy (TLE), Alzheimer’s disease and healthy controls using a convolutional neural network algorithm applied to magnetic resonance imaging (MRI) scans. People with TLE can be distinguished, including those without easily identifiable TLE-associated MRI features.